Bundled and dispersed carbon nanotube assemblies on graphite superstructures as free-standing lithium-ion battery anodes. (February 2019) - Yan, Yiran; Li, Changling; Liu, Chueh; Mutlu, Zafer; Dong, Bo; Liu, Jingjing; Ozkan, Cengiz S.; Ozkan, Mihrimah
Abstract: Carbonaceous materials are intensively used as additives or active electrode materials in lithium-ion battery (LIB) industry due to their stable chemical and physical properties. Compared to developing next-generation high-capacity non-carbonaceous anode materials, improvement on current carbonaceous materials could lead to instant commercial values due to less process modifications to the battery manufacturing. Here, we report a facile approach to synthesize carbon nanotubes (CNTs) with controlled assemblies: well-dispersed CNTs vs. bundled CNTs. Furthermore, we incorporated these CNTs onto three-dimensional (3D) graphite foams as free-standing anodes for LIBs. This hierarchical 3D network provided high surface area and ultra-high conductivity with enhanced battery capacity. With controlled growth conditions, the assembly of CNTs can be changed from bundled state to dispersed state, resulting in a significant improvement in electrochemical performance. The dispersed CNTs showed a higher specific capacity of above 800 m A h g − 1 over 120 cycles, while CNT bundles exhibited a specific capacity of 500 m A h g − 1 . The loose structure of well-dispersed CNTs provides sufficient active interfaces between electrolyte and materials, as well as shortened ion transport path. Insights can be gained in improving state-of-the-art battery performance by controlling the bulk assemblies of CNT additives. Graphical abstract: Image 1